FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUSIRAN UNITED STATES AGENCY FOR INTERNATIONAL DEVELOPMENT (USAID) DI BOLIVIA - Rafdi "; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research explains about relationship between the United States with Bolivia, as well as the influence of USAID in Bolivia that led government under the leadership of the Bolivian government of Evo Morales taking action to expel USAID from Bolivia. Bolivia is one of the poorest countries in Latin America. Dependence of Bolivia to the United States as a major donor to the country's development of Bolivia, as well as American interests to stability in Latin America in Bolivia has made relations between the two countries became close. However, after the election of Evo Morales as President of Bolivia in 2005, has changed the dynamics of politics in Bolivia. It is not directly influence the relationship the United States and Bolivia due to the Bolivian government has always been pro-United States actually began as anti-United States.The author analyzes this case by finding data and facts through some literatures. The literature was collected from books, journals, media and website. Theory that is used in analyzing expelled USAID from Bolivia is the theory of foreign policy with the decision making models by Richard SnyderFrom this research can be seen as factors that the Bolivian government take action to expel USAID. Factors stabilized ideology and political Bolivia is one reason for the Bolivian government took measures to expel the aid agencies of Bolivia. In addition, the attitude of the United States which sees countries in Latin America as the "backyard" for Americans has sparked action Bolivian President to take such measures.Keywords: USAID, Bolivia, Evo Morales, destabilized, democracy, expel